6ER-012 Persistence for disease modifying drugs for multiple sclerosis. (24th March 2020) - Rodrigues, M; Soares, A; Almeida, P; Alcobia, A; Vargas Gomes, M; Andreozzi, V; Félix, J
Abstract : Background and importance: Persistence of therapy is fundamental to achieve disease management goals. Due to the chronic nature of multiple sclerosis treatment, interventions by hospital pharmacists is fundamental to patient persistence with disease modifying drugs (DMD), reducing relapses and slowing disease progression. Aim and objectives: The study aimed to assess persistence for multiple sclerosis therapy. Material and methods: This was a retrospective cohort study based on hospital drug claims for multiple sclerosis. Patients with at least one claim for interferon, fingolimod, dimethyl fumarate, glatiramer acetate, natalizumab or teriflunomide were eligible if naïve or had switched between 2012 and 2017. Naïve were defined as patients without any claim in the previous 365 days. Switchers were defined as patients who changed to other drugs anytime during the study period (2012–2017). The main outcome was persistence, defined as time from initiation to discontinuation of a given DMD, which was considered as a gap in therapy when a subsequent claim for the same drug occurred >90 days after the end of the previous claim. The proportion of persistent patients was reported for 6 and 12 months. Time to event analysis was performed with the Kaplan–Meier estimator and semi-parametric Cox proportional hazard regression model. Results: A total of 87 patients were included with a mean age of 43.0 (SD 10.9), of whom 44.8% (n=39) were naïve and 55.2% (n=48) were switchers. Overall, 55.2% of patients were receiving treatment with injectable drugs (glatiramer acetate 24.1%; interferon 23.0%; natalizumab 8.1%) and 44.8% with oral drugs (fingolimod 19.5%; teriflunomide 18.4%; dimethyl fumarate 6.9%). For the overall sample, median time to discontinuation was 4.5 years. Median time to discontinuation for injectable DMD was significantly lower (median 1.2 years) than for oral DMD (median not reached) (log rank <0.001). The risk of discontinuing treatment was 10.0 times higher for patients receiving treatment with injectable DMD compared with oral DMD (HR=10.0, 95% CI 3.0 to 33.5). The probability of persistence for injectable DMD decreased substantially from 6 months (70.2%, 95% CI 57.2% to 86.1%) to 12 months (52.5%, 95% CI 37.9% to 72.9%). Conclusion and relevance: Treatment with oral drugs was associated with higher persistence in patients with multiple sclerosis. References and/or acknowledgements: No conflict of interest.